Development and Implementation of a Supervisor Strategy and Sliding Mode Control Setup for Fuel Cell-Based Hybrid Generation Systems - Moré, Jerónimo José (2015)
This paper presents the development and experimental results of a supervisor strategy and a sliding mode control setup to improve the performance of hybrid generation systems. The topology in this study is conformed by a core comprising a fuel cell module and a supercapacitor module, in combination with an alternative energy source module and an electrolyzer. In particular, a wind power turbine is considered as alternative power source to attain a hybrid generation system fully relying on renewable energy. First, a supervisor strategy is proposed to manage the power flows of the subsystems and coordinate the system as a whole. Subsequently, a sliding mode control setup for combined operation of the dc/dc power converters of the fuel cell/supercapacitor core is presented to track the power references synthesized by the supervisor control. Both control levels, supervisor strategy and sliding mode controllers, are implemented and assessed through extensive experimental tests under different wind conditions and heavy-load changes.